1965
DOI: 10.1002/app.1965.070090204
|View full text |Cite
|
Sign up to set email alerts
|

Methyl α‐cyanoacrylate. II. Copolymerization studies

Abstract: synopsisCopolymerization of methyl a-cyanoacrylate with five reference monomers gave values e = +2.1 and of log Q = 0.65, with much scatter in the latter value. Alternating copolymers are formed by copolymerization with monomers of e = -0.8 or less. Bulk copolymerization with such monomers could not be accomplished, aa a rapid noncatalyzed polymerization occurred upon mixing even at 0°C. Random copolymers with methyl methacrylate could be prepared in bulk; those with ca. 10% methyl methacrylate had physical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…4. In the literature several conflicting values of a glass transition temperature (T g ) of PVP were found ranging from 54 8C to 175 8C [14][15][16][17][18][19]. These may be attributed to the large influence of sorbed moisture due to the hydrophilic nature of the material, as will be shown by present measurements.…”
Section: Dsc Thermograms Of the Blendsmentioning
confidence: 78%
“…4. In the literature several conflicting values of a glass transition temperature (T g ) of PVP were found ranging from 54 8C to 175 8C [14][15][16][17][18][19]. These may be attributed to the large influence of sorbed moisture due to the hydrophilic nature of the material, as will be shown by present measurements.…”
Section: Dsc Thermograms Of the Blendsmentioning
confidence: 78%
“…It was found that poly(ECA‐ co ‐MMA) with various compositions ranging from homo‐polyECA, poly(ECA(10%)‐ co ‐MMA(90%)), polyECA(20%)‐ co ‐MMA(80%)), all the way to homo‐polyMMA, could be synthesized with compositions, which were the same as the feed ratio of the two comonomers. On the other hand, Kinsinger reported that for copolymerization of MCA ( M 1 ) and MMA ( M 2 ) in benzene at 60 °C, the values of the corresponding reactivity ratios, r 1 and r 2 , were 0.25 and 0.04, respectively . Assuming ECA had a similar reactivity to MCA, the reactivity ratios for ECA and MMA should be relatively small, which would force the random copolymerization to show a tendency to follow alternating copolymerization behavior.…”
Section: Resultsmentioning
confidence: 99%
“…A noticeable exception to the last rule is methyl a-ethylthioacrylate H2C--C(SEt)COOMe, whose 1/r 2 value of >100 [70] is higher than the values for the very electrophilic methyl ~-cyanoacrylate H2C=C(CN)COOMe (1/rz = t00) [101] and diethyl methylenemalonate H2C = C(COOEt)2 (1/rz = 33) [96,98]. As mentioned above its equivalent in the Correlations similar to Hammett relationships have been described in the literature for some 1,1-disubstituted olefins including captodative ones [96,98].…”
Section: Radical-initiated Copolymerization Of Captodative Oiefinsmentioning
confidence: 85%